Emancipatory Feminism in the Time of Covid-19 Transformative resistance and social reproduction - Azeez, Hawzhin (Democratic Marxism, 2023)
The Covid-19 pandemic threw into stark relief the multi-dimensional threats created by neoliberal capitalism. Government measures to alleviate the crisis were largely inadequate, leaving women - in particular working-class women - to carry the increased burden of care work while at the same time placing themselves in direct risk as frontline workers. Emancipatory Feminism in the Time of Covid-19, the seventh volume in the Democratic Marxism series, explores how many subaltern women - working class, peasant and indigenous - challenge hegemonic neoliberal feminism through their resistance to ordinary capitalist practices and ecological extractivism. Contributors cover women's responses in a wide range of contexts: from women leading the defence of Rojava - the Kurdish region of Syria, to approaches to anti-capitalist ecology and building food secure pathways in communities across Africa, to championing climate justice in mining affected communities and transforming gender divisions in mining labour practices in South Africa, to contesting macro-economic policies affecting the working conditions of nurses. Their practices demonstrate a feminist understanding of the current systemic crises of capitalism and patriarchal oppression. What is offered in this collection is a subaltern women's grassroots resistance focused on advancing and enabling solidarity-based political projects, deepening democracy, building capacities and alliances to advance new feminist alternatives.